PESTICIDE HAZARDS AND SAFE APPLICATION TECHNIQUES FOR FARMERS AND THE ENVIRONMENT IN SUSTAINABLE AGRICULTURE - Joshua Theo Anugerah Siahaan; Felisa Rizky Amalia; Muhammad Ashfal Ashfiya; Darren Shevandra Syamsir; Amalia Azzahroh; Muhammad Bagas Ikmal Rifki; Sani (jses, 2025)
The unsafe and improper use of pesticides among farmers can pose various health and environmental risks. In order to increase farmers’ awareness and understanding of the dangers as well as the safe use of pesticides, a community service program was carried out in Giripurno Village, Bumiaji District, Batu City. This program included socialization and training involving 17 local farmers. The activities covered the delivery of materials on types of pesticides, their negative impacts, and correct and safe application techniques. An evaluation was conducted through pre-tests and post-tests to measure the improvement in participants’ knowledge. The results showed a significant increase in farmers’ understanding of pesticide hazards and their safe usage. This program is expected to help farmers adopt safer and more sustainable agricultural practices, while also protecting their health and the surrounding environment.